2020
DOI: 10.31964/mltj.v1i1.291
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Activity of Annona muricata Linn Leaves Ethanolic Extract (AMEE) on T47D Breast Cancer Cell Line

Abstract: Breast cancer is the most common cancer in women throughout the world, with new cases and deaths which continue to increase. Soursop leaves (Annona muricata L) have been used extensively in traditional medicine, including cancer. Acetogenin, alkaloids, and phenols contained in soursop leaves are known to have anti-cancer effects. Among them, acetogenin has the most dominant role and reported to have a cytotoxic effect on various cancer cell lines. This study aims to determine the cytotoxic activity of soursop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…13 +2 +2 +2 +1 +2 +2 +2 +1 +1,75 1 Low Risk of Bias Fertilita, dkk. 14 +2 +2 +2 +2 +2 +2 +2 +1 +1,875 1 Low Risk of Bias Suhendar U. 15 +2 +2 +2 +2 +2 +2 +2 +1 +1,875 1 Low Risk of Bias Ibrahim A.A., dkk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13 +2 +2 +2 +1 +2 +2 +2 +1 +1,75 1 Low Risk of Bias Fertilita, dkk. 14 +2 +2 +2 +2 +2 +2 +2 +1 +1,875 1 Low Risk of Bias Suhendar U. 15 +2 +2 +2 +2 +2 +2 +2 +1 +1,875 1 Low Risk of Bias Ibrahim A.A., dkk.…”
Section: Discussionmentioning
confidence: 99%
“… Fertilita, dkk. 14 2020 S2 Annona muricata (Soursop) Note: Ethanol extract East Java T47D cell Breast cancer MTT Assay Decreases BCL2 protein regulation, increases Bax, inhibits mitochondrial I complexes, and inhibits NADH ubiquinone-oxidase on the plasma membrane of cancer cells causing apoptosis The IC50 value of Annona muricata leaf ethanol extract against T47D cancer cells was 109.91±3.04 μg/mL Soursop (Annona muricata) leaf ethanol extract has the potential to inhibit the proliferation of T47D cancer cells 3. Suhendar U.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Daddiouaissa et al (2019) found that A. muricata fruit ionic liquid extract displayed an anti-proliferative effect on MCF-7 breast tumor cell lines by inducing apoptosis, arresting the cell cycle and lowering the number of new cells generated. Ethanolic extract of A. muricata inhibits T47D cell proliferation (Fertilita et al 2020), stimulates mitochondrial cell death, inhibits cell growth, & reduces cellular motility in MDA cells (Kim et al 2018). The IC50 value of the methanolic extract of A. muricata leaves was 85.55 g/mL against the MCF-7 cell line (Naik and Sellappan 2021).…”
Section: Annona Muricatamentioning
confidence: 99%
“…9 Flavonoids were found to induce apoptosis more strongly than the clinically proven anti-tumour agent Camptothecin. 10,11 A previous study showed the cytotoxic activity of A. muricata leaf extract with ethanol, ethyl acetate and hexane fractions against cervical cancer (HeLa) cell lines at concentrations of 1.5 µg/mL, 3.125 µg/mL, 6.25 µg/mL, 12.5 µg/mL, 25 µg/mL, 50 µg/mL, 100 µg/mL and 200 µg/mL. 12 The leaves of the A. muricata have been investigated extensively for their diverse pharmacological applications and were found to be superior for their anti-inflammatory and anticancer properties.…”
Section: Introductionmentioning
confidence: 99%